Effect of Commercial Fertilizers on the Natural Grasslands on Deep Alluvial Soils in the Ambala Siwaliks - Erasmus, I. I.; Sud, A. D. (Indian Forester, 1976)
It has been shown that application of commercial fertilizers increases the total forage production of natural grasslands on deep alluvial soils in the Ambala Siwaliks. Application of Nitrogen and Phosphorus in combination at the rate of 22.75kg per hectare resulted in significandy increased yields. The application of fertilizers also induced changes in the botanical composition of the grasslands, resulting in an increase in the proportion of the more succulent and nutritious grasses at the cost of the coarser grasses, Heteropogon contortus and Eremopogon foveoatus.